If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9t + -15 = 7t + 11 Reorder the terms: -15 + 9t = 7t + 11 Reorder the terms: -15 + 9t = 11 + 7t Solving -15 + 9t = 11 + 7t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-7t' to each side of the equation. -15 + 9t + -7t = 11 + 7t + -7t Combine like terms: 9t + -7t = 2t -15 + 2t = 11 + 7t + -7t Combine like terms: 7t + -7t = 0 -15 + 2t = 11 + 0 -15 + 2t = 11 Add '15' to each side of the equation. -15 + 15 + 2t = 11 + 15 Combine like terms: -15 + 15 = 0 0 + 2t = 11 + 15 2t = 11 + 15 Combine like terms: 11 + 15 = 26 2t = 26 Divide each side by '2'. t = 13 Simplifying t = 13
| 2x-7=x+3 | | 9t-15=11+4 | | 2x+14=-x-1 | | -7=x+3 | | 9t-15=7+11 | | 5x-10+x=2 | | 6x+17=16x-63 | | 4x-2(x+9)=2 | | 6t-13=4+11 | | 11x+8=7x+36 | | 4x+5(x-9)=0 | | 13t-11=6+4 | | 6x+12=108-6x | | x+14=8(x+7) | | x+14=8(x+6) | | 0.5x^2-x-0.25=0 | | -30n=-27n-12 | | 2y^2-3y=-4 | | 2y^2-3y=4 | | 4a+10=8a+5 | | 0.5x-3+x=15 | | ln(x-1)+ln(x+5)=0 | | 6x^2=4-5x | | 5x+17=x-11 | | 3(h-6)=2(5-2h) | | 8x-12=4x | | 7y-3=4y+9 | | 2(x-1)=3x-1-x | | 4x+80=2x-20 | | 6.4T=64 | | (x^4)-(45*x^3)+(560*x^2)-(1380*x)+864=0 | | t^2=18 |